An Assessment of the Level of Awareness of Eye Health Care Services Provided by Onesight in the Gambia - Fanneh, Momodou Mustapha; Belford, Christopher; Sanyang, Lang; Camara, Bumi; Dibba, Yusupha (International Journal of Emerging Trends in Social Sciences, 2022)
The objective of the Scorecard study was to assess the intervention of OneSight with respect to Awareness of their services in The Gambia and the perception of Gambians on eye care in The Gambia. More specifically in this paper, the scorecard assesses the level at which people are aware of the existence, the activities and the services offered by OneSight in The Gambia. The research employed both quantitative and qualitative methods. The study revealed that the majority of the sampled respondents are aware of refractive error i.e., about 90%. Their major source of information about eye care issues was through radio however, they gather important information from other sources such as healthcare workers and television. Most of the respondents who are aware of eyesight-related problems, typically obtained information through Government clinics, only 2.8% got their information from OneSight. It was also discovered that 94.6% of the respondents sought eye care treatment from health facilities as opposed to a home or local treatments. Based on the findings, practical implications and an agenda for future research are suggested. For instance, it is recommended that OneSight should strengthen community outreach programs, improve its communication strategies, create more visibility, and conduct more publicity events for more awareness about its programme and activities.